Memórias, emoções e sentimentos: os processos cognitivos sob a perspectiva do professor no desenvolvimento da aprendizagem - Oliveira, Kellen Vitória Costa de (Brasil, 2024)
This is a scientific investigation, with the objective of identifying and analyzing the influence of the cognitive processes of memory, emotion and feeling on the learning development of child victims of sexual violence in a public school in the city of Manaus in the State of Amazonas. The discussion of this theme is due to the following problem: what is the participation of the cognitive processes of memory, emotion and feeling during the learning development of child victims of sexual violence in the school context of the city of Manaus? To answer the question, we adopted the following specific objectives: a) understand the development of the cognitive processes of memory, emotion and feeling using literature from the fields of cognitive psychology and cognitive neuroscience; b) Investigate and interpret how teachers see the relationship between memory, emotion and feeling in the learning development of children who are victims of sexual violence in elementary school I; c) Reflect the implications of the cognitive processes studied in the learning development of child victims of sexual violence. To achieve them, we turned to the literature of Neuroscience and Cognitive Psychology, which is theoretical, bibliographic and field-based. This is a qualitative, descriptive and exploratory study. Year after year, the rate of reports of violence increases in society. Many of these cases are discovered during the student's presence in the school field, and although it is a space for struggle and transmission of knowledge, there is still a certain reluctance on the part of the community, and at the same time, a desire for changes in this very sensitive debate, and increasingly present in the lives of our children.